Videolaryngoscopy versus Fiber-optic Intubation through a Supraglottic Airway in Children with a Difficult Airway: An Analysis from the Multicenter Pediatric Difficult Intubation Registry. (September 2017) - Burjek, Nicholas E.; Nishisaki, Akira; Fiadjoe, John E.; Adams, H. Daniel; Peeples, Kenneth N.; Raman, Vidya T.; Olomu, Patrick N.; Kovatsis, Pete G.; Jagannathan, Narasimhan; Hunyady, Agnes; Bosenberg, Adrian; Tham, See; et al.
Abstract : Background: The success rates and related complications of various techniques for intubation in children with difficult airways remain unknown. The primary aim of this study is to compare the success rates of fiber-optic intubation via supraglottic airway to videolaryngoscopy in children with difficult airways. Our secondary aim is to compare the complication rates of these techniques. Methods: Observational data were collected from 14 sites after management of difficult pediatric airways. Patient age, intubation technique, success per attempt, use of continuous ventilation, and complications were recorded for each case. First-attempt success and complications were compared in subjects managed with fiber-optic intubation via supraglottic airway and videolaryngoscopy. Results: Fiber-optic intubation via supraglottic airway and videolaryngoscopy had similar first-attempt success rates (67 of 114, 59% vs . 404 of 786, 51%; odds ratio 1.35; 95% CI, 0.91 to 2.00; P = 0.16). In subjects less than 1 yr old, fiber-optic intubation via supraglottic airway was more successful on the first attempt than videolaryngoscopy (19 of 35, 54% vs . 79 of 220, 36%; odds ratio, 2.12; 95% CI, 1.04 to 4.31; P = 0.042). Complication rates were similar in the two groups (20 vs . 13%; P = 0.096). The incidence of hypoxemia was lower when continuous ventilation through the supraglottic airway was used throughout the fiber-optic intubation attempt. Conclusions: In this nonrandomized study, first-attempt success rates were similar for fiber-optic intubation via supraglottic airway and videolaryngoscopy. Fiber-optic intubation via supraglottic airway is associated with higher first-attempt success than videolaryngoscopy in infants with difficult airways. Continuous ventilation through the supraglottic airway during fiber-optic intubation attempts may lower the incidence of hypoxemia. Abstract : A clinical registry collecting information of 1, 603 pediatric anesthesia cases with difficult tracheal intubation with conventional direct laryngoscopy revealed similar first-attempt success rates for fiber-optic intubation via supraglottic airway and videolaryngoscopy, whereas the former was more successful than the latter in infants.Supplemental Digital Content is available in the text.